Analysis of Factors Associated with the Incidence of Hypertension in the Working Area of Wara Utara Community Health Center, Palopo City - Harleli Harleli (Jurnal Kesehatan dan Kedokteran, 2026)
Hypertension is a major public health problem because it often occurs without specific symptoms and may lead to severe complications, including stroke, kidney failure, and cardiovascular disease. Dietary behavior and psychological stress are modifiable factors that may contribute to increased blood pressure, particularly in communities served by primary health care facilities. Objective: This study aimed to analyze the association between sodium dietary intake, stress level, and the incidence of hypertension in the working area of the Wara Utara Community Health Center, Palopo City. Methods: This study used a quantitative analytic observational design with a cross-sectional approach. The sample consisted of 97 respondents aged 35–65 years selected using purposive sampling. Data were collected through blood pressure measurement, sodium intake assessment using a Semi-Quantitative Food Frequency Questionnaire, and stress level measurement using the Depression Anxiety Stress Scales questionnaire. Data were analyzed using univariate analysis, Chi-square test, and binary logistic regression. Findings: The results showed that 70 respondents (72.2%) had hypertension, 37 respondents (38.1%) had excessive sodium intake, and 52 respondents (53.6%) experienced stress. Sodium dietary intake was significantly associated with hypertension (p = 0.007), and stress was also significantly associated with hypertension (p < 0.001). Multivariate analysis showed that stress was the most dominant factor associated with hypertension (OR = 6.71; 95% CI: 2.01–22.38; p = 0.005), followed by excessive sodium intake (OR = 5.13; 95% CI: 1.61–16.32; p = 0.020). Implications: These findings imply that hypertension prevention programs at the primary health care level should integrate sodium intake control, healthy dietary education, routine blood pressure monitoring, and stress management. Originality: The originality of this study lies in its simultaneous analysis of dietary and psychosocial factors associated with hypertension in a local primary health care setting, providing contextual evidence for community-based hypertension prevention strategies.